The ankle–brachial index and risk of incident stroke in Chinese hypertensive population without atrial fibrillation: A cross‐sectional study - Shi, Yumeng (J Clin Hypertens (Greenwich), 2020)
We aimed to evaluate the relation of the ankle–brachial index (ABI) with the prevalence of stroke and to examine any possible effect modifiers among hypertensive patients without atrial fibrillation. A total of 10 750 subjects with hypertension aged 27‐96 years were included in the current study. The outcome was a stroke. Odds ratios of stroke concerning ABI were calculated using multivariate logistic regression models. Among 10 750 hypertensive participants, 690 (6.42%) had a stroke. Multivariate logistic analyses showed that ABI was negatively correlated with the prevalence of stroke (per SD increment; adjusted OR, 0.88; 95% CI, 0.82‐0.94). Compared with participants in Q 1, the odds ratios (95% CI) for those in the Q2 (1.05 to 1.10), Q3 (1.10 to 1.15), and Q4 (≥1.15) were 0.71 (0.56, 0.90), 0.87 (0.70, 1.08), and 0.81 (0.65, 1.01), respectively. However, compared with higher ABI value, lower ABI value (<1.05) would significantly increase the odds of stroke (OR: 1.26, 95% CI [1.05‐1.50]), especially in the elderly over 65 years old. A generalized additive model and a smooth curve fitting showed that there existed an L‐shaped association between ABI and the prevalence of stroke. Our results suggest that an L‐shaped association between ABI and the prevalence of stroke was found in general hypertensive patients, with a turning point at about 1.05. Compared with higher ABI value, lower ABI value (<1.05) would significantly increase the prevalence of stroke (OR: 1.26, 95% CI [1.05‐1.50]), especially in the elderly over 65 years old.